Dasatinib, a rare cause of drug-induced chylothorax - San Martín, Pablo D.; Lamot, Sebastián; Sibon, Flavia C.; Álvarez, Álvaro J.; Eriguren, Verónica; Bernardino, Augusto (Revista Argentina de Cirugía, 2026)
Chylothorax is the extravasation of milky chyle rich in triglycerides into the pleural cavity. The etiology of chylothorax includes malignant obstructions and lymphatic pleural fistulas due to thoracic surgery or trauma. Ten percent of the cases are idiopathic and is considered a rare occurrence resulting from drug use. We report the case of a 31-year-old male patient with a history of chronic myeloid leukemia treated with dasatinib, who presented with cough and progressive dyspnea, with no other symptoms. The chest X-ray and computed tomography showed right pleural effusion. Thoracocentesis yielded cloudy and milky-white pleural fluid. Biochemical analysis of the pleural fluid revealed the presence of chylothorax. Conservative treatment was the first therapeutic option with a dietary plan supplemented with mediumchain triglycerides, followed by pleural drainage and discontinuation of dasatinib, pleurodesis and switch to bosutinib. At two years of follow-up, chylohorax or pleural effusion did not recur.